Inpatient and Outpatient Satisfaction Comparison of Radiology Installation Service Quality at Private Hospital - Mustika Fatimah; Muslimah Putri Utami; Septi; Yola Erista; Maurend Yayank Lewinsca (Science Midwifery, 2022)
The challenge faced by a hospital during undercontrolled the Covid-19 pandemic is to continue to provide health services quality, in this case, radiology installation service, with patient outcomes being satisfied with the existing services. The purpose of this study was to analyze inpatient and outpatient satisfaction comparison of radiology installation service quality at private hospital. Methods: This analytic survey research used a cross sectional approach. The samples were taken by total sampling method on as many as 30 inpatients and 30 outpatients in private hospital. Statistical data analysis using SPSS Independent T Test for satisfaction comparison and Mann Whitney U Test for various dimensions of service comparison. Results: There was no significant difference in satisfaction (Sig. value 0.136) and various dimensions such as reliability, responsiveness, assurance, empathy, and tangibles of service (Sig. value 0.945; 0.267; 0.134; 0.516; 0.163) between inpatients and outpatients at private hospital. Conclusion: Hospital must improve the quality of all dimensions of radiology installation service to increase all patients satisfaction, not only inpatient but also outpatient satisfaction.